การตอบสนองฉับพลันของการแบกน้ำหนักกระโดดด้วยความหนักแตกต่างกันที่มีต่อพลังในนักกีฬาวอลเลย์บอลหญิง - เมลานี อุระสนิท (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
Purpose The purpose of this study was to study and compare the responses to squat jump with different weights on power in female volleyball players.            Methods Subjects were ten volleyball female players, age between 18 – 25 years old with relative strength above 1.5. The squat jumps performance, with a 110 degree angle, was measured in three conditions, consist of 0%, 10% and 20% of 1RM with 20 squat jumps as maximum effort and rest 5 second between each jump. The jumping performance, including average peak power, peak force and peak velocity during squat jumps was once a week in a counter-balance order. The data were analyzed by One-way Anova of variance with repeated measure and presented as means and standard deviation.            Results of the study shows that; the average peak power of squat jumps were occurred at 0% and 10% which show the average peak power greater than 20% was significantly at the .05 level (P<0.05). The average peak force of squat jumps at weight 0% and 20% show higher average peak force than 10% (P<0.05). And the average peak velocity was occurred at weight 0%, show the average peak velocity greater than 10% and 20% (P<0.05).            Conclusion, the power for squat jumps with weight in female volleyball players at weight 0% and 10% has the peak power greater than weight 20%.